Using Information Gap Activity to Increase Students' speaking Skill at the Twelve Grade of MAN 1 Pamekasan - Ansharul Fuqaha; Abd Ghofur (IAIN MADURA, 2015)
Based on the researchers’ observation on the preliminary study on the teachingof speaking, the problem was found that the students’ speaking skill in the teaching and learning was very low. It was because the class was heterogeneousand the teacher used monotonous teaching activity. To cope of this problem, theresearcher employed the Information gap activity. This study tries to prove how the Information-gap activity can increase students’ speaking skill at the thirdgrade of MAN 1 Pamekasan. The study was design to increase the students’speaking skill by using Information gap activity at MAN 1 Pamekasan. Thestudy was collaborative classroom action research in which the researcher andthe collaborator worked together, the researcher acted as the teacher while thecollaborator observed the students during the implementation of the strategy. This study was conducted in one cycle consisting of six meetings using thefollowing procedures; planning, implementing, observing and reflecting. The data of the study were collected through the observation checklists, field notes,and questionnaires. The subject of the study were 41 students of third grade on science 3 program MAN 1 Pamekasan.